Epigenetic regulation of memory formation and maintenance - Zovkic, Iva B. (Cold Spring Harbor Laboratory Press, 2013)
Understanding the cellular and molecular mechanisms underlying the formation and maintenance of memories is a central goal of the neuroscience community. It is well regarded that an organism's ability to lastingly adapt its behavior in response to a transient environmental stimulus relies on the central nervous system's capability for structural and functional plasticity. This plasticity is dependent on a well-regulated program of neurotransmitter release, post-synaptic receptor activation, intracellular signaling cascades, gene transcription, and subsequent protein synthesis. In the last decade, epigenetic markers like DNA methylation and post-translational modifications of histone tails have emerged as important regulators of the memory process. Their ability to regulate gene transcription dynamically in response to neuronal activation supports the consolidation of long-term memory. Furthermore, the persistent and self-propagating nature of these mechanisms, particularly DNA methylation, suggests a molecular mechanism for memory maintenance. In this review, we will examine the evidence that supports a role of epigenetic mechanisms in learning and memory. In doing so, we hope to emphasize (1) the widespread involvement of these mechanisms across different behavioral paradigms and distinct brain regions, (2) the temporal and genetic specificity of these mechanisms in response to upstream signaling cascades, and (3) the functional outcome these mechanisms may have on structural and functional plasticity. Finally, we consider the future directions of neuroepigenetic research as it relates to neuronal storage of information.